Criterion-related validity of the Sugar- Sweetened Beverage (SSB) questionnaire among children and adolescents in Malaysia - Bakeri, Nur Arina; Amirullah, Nur Amalina; Sulaiman, Norhasmah; Gan, Wan Ying; Loh, Su Peng; Ahmad Fuzi, Salma Faeza; Shafie, Siti Raihanah; Ibrahim, Nazli Suhardi; Mohamad, Fatimah Zurina; Selamat, Rusidah (Springer Science and Business Media LLC, 2024)
Sugar-sweetened beverages (SSBs) are a major source of dietary sugar, and their consumption is on the rise among children and adolescents. Excessive sugar intake is a significant contributor to overweight, obesity, and non-communicable diseases (NCDs). The consumption of SSBs, particularly that of children and adolescents, has been of interest as of late, as they are implicated in affecting body weight status. Thus, the goal of this study was to determine the predictive criterion-related validity of the SSB questionnaire that was administered to children and adolescents to assess their SSB and non-SSB intake. A nationwide crosssectional study involving 5211 respondents aged 7-17 years old and their parents was conducted. The selfadministered Malay questionnaire was distributed to collect information on socioeconomic background, the frequency of eating out at restaurants or other food premises, the availability of SSBs at home, and SSB consumption patterns of children and adolescents within a week. The predictive criterion-related validity was determined by using six hypotheses that can differentiate between two independent sample means of SSB consumption based on age, gender, locality, monthly household income, frequency of eating out at restaurants or other food premises, and availability of SSBs at home. The independent samples t-test and one-way ANOVA were used to conduct the validation process. Five out of six hypotheses were accepted. Significant mean differences were observed between sociodemographic factors, such as age (t=-10.56, p<0.001), localities (t=-5.37, p<0.001), monthly household income (F=26.83, p<0.001), and SSB consumption. Behavioural factors, including eating out at restaurants or other food premises (t=9.93, p<0.001) and environmental factors such as the availability of SSBs at home (F=136.24, p<0.001) also showed a significant difference with SSB consumption. The SSB questionnaire demonstrated the ability to differentiate between groups. Thus, this SSB questionnaire appears to be valid to measure the SSB consumption of children and adolescents.